Uptake of protective tetanus toxoid vaccine doses and maternal associated factors during pregnancy in armed conflict zone, hospital-based cross-sectional study - Kebede Bizuneh, Fassikaw; Muhidin Mustofa, Semira (Frontiers in Reproductive Health, 2024)
Vaccinating pregnant women with tetanus toxoid (TT) is crucial to prevent neonatal tetanus, reducing related deaths by 94%. In conflict zones with restricted access to deliveries, neonates face an 80-100% fatality rate. This study explores TT vaccine protective dose uptake and maternal enriching factors during pregnancy in armed conflicts zone, hospital based cross-sectional study.